The Influence of Accounting Profits on Stock Prices of K211 Sub-Sector Companies Listed on The IDX - PRAYITNO, Yogo Heru; DIANITA, Mirna; HADIAN, Niki (PT Keberlanjutan Strategis Indonesia, 2023)
Currently, the company's performance in delivery services has a significant impact on society. The performance of companies in this sector increases in line with the public's need for the services they offer. This research focuses on 19 companies in the K211 sub-sector (logistics and delivery). From this population, a sample was selected consisting of 8 companies that met specific criteria, such as being listed on the Indonesia Stock Exchange (2017-2022), submitting complete financial reports, and having share price data. Descriptive analysis is carried out with statistics, such as average, maximum, and minimum, for research variables. There are also measurements of accounting profit, return on assets, and the average value of accounting profit. Share price is also considered. This research also includes linear regression analysis that connects profitability as an independent variable with company value as the dependent variable. Certain companies have improved performance, but their stock prices have fallen. It goes against the theory that outperformance will influence stock prices. This research evaluates whether a company's performance influences its share price. This research uses regression analysis to determine the relationship between company performance proxied by accounting profits and share prices of K211 subsector companies. The results show that accounting profits do not affect the stock prices of K211 subsector companies. The significance level of 0.056 is more significant than 0.055.